2022
DOI: 10.1186/s12879-022-07831-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for multidrug resistance in tuberculosis patients with diabetes mellitus

Abstract: Objective To study the risk factors and prediction models of multidrug resistance in patients with tuberculosis and diabetes and those with a history of tuberculosis treatment. Methods A total of 256 tuberculosis patients with diabetes who were registered in Luoyang city, Henan Province, from January 2018 to December 2021. Logistic regression analysis was performed to analyse the risk factors for multidrug resistance. ROC curves were used to analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
1
0
2
Order By: Relevance
“…Tuberculosis is a common chronic disease threatening human health caused by Mycobacterium tuberculosis infection, which mainly affects the glucose metabolism of diabetic patients and aggravates the condition; at the same time, fever and other toxic symptoms caused by tuberculosis infection can lead to impaired pancreatic islet β-cell function, which reduces the function of insulin receptor and affects the secretion function of pancreatic islets [9]. Related studies have shown that gender and duration of diabetes are risk factors for PTB combined with T2DM [10] [11], and that men and long duration of disease are at higher risk of developing TB and diabetes. Therefore, this study excluded the effect of gender and disease duration, (in order to avoid the influence of the difference between the two groups of gender and the course of diabetes on the relationship between the disease and the factors, so as to more truly reflect the relationship between the research factors and the disease, therefore, this study adopted a 1:1 matching method according to gender and the course of diabetes, which can not only control the influence of confounding factors, but also improve the efficiency of the study and ensure the comparability between the study group and the control group.)…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis is a common chronic disease threatening human health caused by Mycobacterium tuberculosis infection, which mainly affects the glucose metabolism of diabetic patients and aggravates the condition; at the same time, fever and other toxic symptoms caused by tuberculosis infection can lead to impaired pancreatic islet β-cell function, which reduces the function of insulin receptor and affects the secretion function of pancreatic islets [9]. Related studies have shown that gender and duration of diabetes are risk factors for PTB combined with T2DM [10] [11], and that men and long duration of disease are at higher risk of developing TB and diabetes. Therefore, this study excluded the effect of gender and disease duration, (in order to avoid the influence of the difference between the two groups of gender and the course of diabetes on the relationship between the disease and the factors, so as to more truly reflect the relationship between the research factors and the disease, therefore, this study adopted a 1:1 matching method according to gender and the course of diabetes, which can not only control the influence of confounding factors, but also improve the efficiency of the study and ensure the comparability between the study group and the control group.)…”
Section: Discussionmentioning
confidence: 99%
“…Data-data tersebut kemudian akan dianalisis menggunakan analisis regresi logistik multivariabel. Hasil penelitian menunjukkan bahwa faktor risiko terjadinya resistensi multidrug pada pasien tuberkulosis dan diabetes adalah Usia<65 tahun, HbA1c yang tinggi, dan riwayat pengobatan tuberkulosis (18).…”
Section: Cunclassified
“…Además de otras intervenciones, para el control de la tuberculosis es necesario lograr el éxito en el tratamiento, ya que los pacientes con antecedentes de incumplimiento del tratamiento o recaída de la infección tienen mayor riesgo de presentar tuberculosis resistente y multirresistente (8)(9)(10). Sin embargo, el éxito terapéutico puede dificultarse por las características sociodemográficas de la población como sexo, edad, condición económica, vulnerabilidad, etnia y, en Colombia, tener seguro de salud subsidiado o no tener ningún seguro.…”
unclassified